Pengaruh Perubahan Lahan Terhadap Tingkat Total Suspended Solid Di Muara DAS Wanggu - Muhammad Amaluddin Nurjayadi; L.M Iradat Salihin; Fitra Saleh; L.M Golok Jaya; Jufri Karim (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
Changes in land use can affect the Total Suspended Solids (TSS) in river water. Higher erosion levels due to land clearing result in increased TSS levels. This study was conducted at the Wanggu River Basin Estuary in 2014 and 2023, with the aim of understanding land use changes, determining TSS distribution, and assessing the impact of land use changes on TSS levels. The data used include land use maps from 2014-2023 derived from Landsat imagery for 2014 and 2023, and TSS data obtained from field surveys. The data were analyzed using overlay and quantitative descriptive methods. The results of the study indicate that the total land use change in the Wanggu River Basin from 2014 to 2023 covers an area of 6,570 hectares (19.28%) of the total Wanggu River Basin area. The highest land use change occurred in forest areas, which decreased by 2,054.39 hectares (6.03%), while the smallest change occurred in water bodies with a reduction of 5.72 hectares (0.02%). The TSS levels in the Wanggu River Basin Estuary increased at 13 observation stations from 2014 to 2023, with the largest TSS change occurring at station 3, where levels rose from 85,439 mg/l (2014) to 142,609 mg/l (2023). The land use changes from 2014 to 2023 have influenced the increase in TSS levels in the Wanggu River Basin due to the significant reduction in forest areas, which has led to higher erosion rates.